Parkinson's Disease Subtypes Show Distinct Tradeoffs Between Response Initiation and Inhibition Latencies. (15th June 2017) - Tolleson, Christopher; Turchan, Maxim; van Wouwe, Nelleke; Isaacs, David; Phibbs, Fenna; Wylie, Scott
Abstract: Objectives: In unpredictable situations, individuals often show tradeoffs between response initiation and inhibition speeds. We tested the hypothesis that Parkinson's disease (PD) motor subtypes differentially impact tradeoffs between these two action-oriented processes. We predicted that, compared to tremor dominant (TD) patients, predominant postural instability and gait dysfunction (PIGD) patients would show exacerbated tradeoffs between response initiation and inhibition in situations requiring the sudden potential need to interrupt an action.Methods: Fifty-one PD patients (subdivided into PIGD [ n =27] and TD [ n =24]) and 21 healthy controls (HCs) completed a choice reaction task to establish baseline response initiation speed between groups. Subsequently, participants completed a stop-signal task which introduced an occasional, unpredictable stop stimulus. We measured changes in initiation speed in preparation of an unpredictable stop (i.e., proactive slowing) and inhibition latency (i.e., stop-signal reaction time).Results: Compared to HCs, PD patients showed slower response initiation speeds in the choice reaction task. All groups showed proactive slowing in the stop-signal task but the magnitude was considerably larger in PIGD patients, almost twice as large as TD patients. PD patients, irrespective of motor subtype, showed longer inhibition latencies than HCs.Conclusions: PIGD and TD subtypes both showed exacerbated response inhibition deficits. However, PIGD patients showed much more pronounced proactive slowing in situations with an expected yet unpredictable need to stop action abruptly. This suggests that PIGD is accompanied by exaggerated tradeoffs between response initiation and inhibition processes to meet situational action demands. We discuss putative neural mechanisms and clinical implications of these findings. ( JINS, 2017, 23, 665–674)